MODEL KONSEP TEORI ADAPTASI CALLISTA ROY PADA ASUHAN KEPERAWATAN DENGAN ANOREXIA NERVOSA - Dayang Laily; Irna Nursanti (Nusantara Hasana Journal, 2024)
This paper aims to explore the application of Callista Roy's adaptation model theory in nursing care for Anorexia Nervosa patients. Anorexia Nervosa is a complex eating disorder with serious impacts on an individual's physical and mental health. Roy's adaptation model has a basic concept that includes four modes of adaptation, namely physiological, self-concept, social role, and interdependence. In the physiological mode, interventions focus on monitoring weight, nutrition, and optimal body function. The self-concept mode emphasizes developing self-esteem and body acceptance. Social roles are maintained through a therapeutic approach that supports positive social interactions. Additionally, interdependence is explored by involving the patient's family and social network in the healing process. By applying Callista Roy's adaptation model theory, nursing care for Anorexia Nervosa patients can become more holistic and integrated. An in-depth understanding of the four modes of adaptation provides a strong foundation for addressing the complex challenges faced by Anorexia Nervosa patients. The practical implication of this paper is the development of nursing care guidelines that are more specific and focused on the unique needs of Anorexia Nervosa patients, while still paying attention to the basic principles of Roy's adaptation model theory.